Structural basis for Smoothened regulation by its extracellular domains - Byrne, Eamon F.X. (Nature, 2016)
Developmental signals of the Hedgehog (Hh) and Wnt families are transduced across the membrane by Frizzled-class G-protein coupled receptors (GPCRs) composed of both a heptahelical transmembrane domain (TMD) and an extracellular cysteine-rich domain (CRD). How such large extracellular domains of GPCRs regulate signalling by the TMD is unknown. We present crystal structures of the Hh signal transducer and oncoprotein Smoothened (SMO), which contains two distinct ligand-binding sites in its TMD and CRD. The CRD is stacked atop the TMD, separated by an intervening wedge-like linker domain (LD). Structure-guided mutations show that the interface between the CRD, LD and TMD stabilises the inactive state of SMO. Unexpectedly, we find a cholesterol molecule bound to SMO in the CRD-binding site. Mutations predicted to prevent cholesterol binding impair the ability of SMO to transmit native Hh signals. Binding of a clinically used antagonist, vismodegib, to the TMD induces a conformational change that is propagated to the CRD, resulting in loss of cholesterol from the CRD-LD-TMD interface. Our work elucidates the structural mechanism by which the activity of a GPCR is controlled by ligand-regulated interactions between its extracellular and transmembrane domains.